Activated tamarind seed coat: a green biosorbent to remove fluoride from aqueous solutions - Dasaiah Srinivasulu (IWA Publishing, 2021)
A novel, inexpensive, easily available and eco-friendly biosorbent, Tamarindus indica activated seed coat, has been evaluated for its capability to remove fluoride from water. Batch experiments were carried out to study the effect of various parameters affecting the biosorption such as pH (2–10), biosorbent dose (0.05 g/L to 0.35 g/L), contact time (10–80 min) and initial fluoride concentration (0.001–0.006 g/L) for the biosorption of fluoride at room temperature. The maximum removal of fluoride was found at pH 6, biosorbent dose 0.3 g and contact time 60 min. Physicochemical characterization studies revealed the suitable morphology and chemical functional groups present on the biosorbent. Isothermal data agreed well with the Langmuir isotherm adsorption model with R2 value 0.976 and KL 0.1. The biosorption interface of fluoride onto Tamarindus indica activated seed coat obeyed the pseudo-second-order rate equation with R2 0.976. The present study demonstrates that Tamarindus indica activated seed coat can effectively remediate fluoride-contaminated water. HIGHLIGHTS Activated tamarind seed coat powder used as biosorbent for the removal of fluoride.; Physicochemical studies of biosorbent revealed favourable features for F removal.; Desorption studies obtained 90% recovery within three cycles.; Developed sorbent applied to real field water samples and succeeded.; This biosorbent can be considered a potential, cost-effective and eco-friendly biosorbent.;